Good Education from Upin Ipin Movie for Children - Girsang, Martina; Verawati Sihombing, Jesisca; Aulia Apriani Sihombing, Maria; Fazar Tumanggor, Tri; Sari Br Ginting, Winda (Lafadz Jaya Publisher, 2023)
The purpose of this study is to find out and analyze the analyzing the film Upin Ipin as a literary work especially to children. This research is a descriptive quantitative whose source comes from several references to data that can be accounted for and can be proven through dialogues in this Upin Ipin film. Upin Ipin's animated series contains many values such as educational values, character, culture, and moral language styles that are very good for children's cognitive development. The real life presented in the film can be well imitated by children because it teaches very positive things.